Effects of Internal Factors on Financial Performance of Joint Venture Banks in Nepal - Ranabhat, Deepesh (Journal of Nepalese Business Studies, 2019)
This paper examines the impact of bank specific variables on financial performance of joint venture banks. The return on assets and return on equity are selected as bank’s performance variables for this study and these two are the dependent variables. Spread rate, size of assets, loan, deposit, liquidity and capital adequacy ratio of the firms are the independent variables. The data are collected from supervision report of Nepal Rastra Bank and annual reports of concerned six banks for 10 years from fiscal year 2008/09 to 2017/18.The pooled OLS multiple regression models are applied to test the significance and effects of bank specific variable on financial performance of Nepalese Joint Venture Banks. The result shows that there is a significant positive impact of interest rate spread on ROA and ROE of the banks. Similarly, there is significant negative impact of asset size on ROA and significant negative impact of liquidity and loan ratio on ROE of the banks.